Synthetic studies directed toward the AB decalin common to HMP-Y1 and hibarimicinone - Hempel, Jonathan E. (Tetrahedron Lett, 2014)
Efforts toward the synthesis of the decalin ring system common to the hibarimicin shunt metabolite HMP-Y1 and parent aglycone hibarimicinone are reported herein. An intramolecular Diels–Alder cyclization rapidly generated the decalin framework. Two approaches toward completion of the AB decalin were vetted. Incorporation of a phenylsulfonyl leaving group β- to both a ketone and a γ-lactone followed by base-induced elimination of sulfinate led to the undesired α,β-unsaturated lactone. Methanolysis of the γ-lactone followed by elimination produced the unexpected bridged cyclic ether by way of an intramolecular oxy-Michael addition of the endo oriented C13 alcohol.